Role of seminars in educational process of secondary schools and high schools. - Yefremov S.V (Kharkov National Pedagogical University, 2011)
The seminar and classification of seminars in secondary school were considered. It was analysed the groups of the seminars, types of the seminars by means of activity, by deductive aim. The seminar is the form of independent scientific and research work which enables the reception of scientific and informative skills during preparation for seminar. Choice of small quantity of a material for a seminar gives possibility for pupils to take the floor with his report, generalizing and proving his point of view and developing logical thinking.